1999
DOI: 10.1103/physrevlett.83.4690
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative to Compactification

Abstract: Conventional wisdom states that Newton's force law implies only four non-compact dimensions. We demonstrate that this is not necessarily true in the presence of a non-factorizable background geometry. The specific example we study is a single 3-brane embedded in five dimensions. We show that even without a gap in the Kaluza-Klein spectrum, four-dimensional Newtonian and general relativistic gravity is reproduced to more than adequate precision.Comment: LaTex, 9 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

164
10,030
7
50

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 7,050 publications
(10,251 citation statements)
references
References 12 publications
164
10,030
7
50
Order By: Relevance
“…(7) and (8) are evaluated at Hubble radius crossing, k = aH (here k is the comoving wavenumber). Defining the spectral indices of scalar and tensor perturbations as…”
Section: Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) and (8) are evaluated at Hubble radius crossing, k = aH (here k is the comoving wavenumber). Defining the spectral indices of scalar and tensor perturbations as…”
Section: Formalismmentioning
confidence: 99%
“…It is now possible also to impose observational constraints on inflation in non-standard cosmologies, the archetypal example being the braneworld cosmology, and in particular the Randall-Sundrum Type II model (RSII) [8] which is the one most investigated in the literature. While it has been shown that observations of the primordial spectra cannot distinguish between the standard cosmology and the braneworld [9], specific constraints on the potential driving inflation will be different between those scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The induced metric on the brane is denoted by γ ab . With the last term in the action (2.1), we have allowed for the contribution of extra field degrees of freedom which are confined to the brane, e.g., the Standard Model fields in a RS2 scenario [3].…”
Section: Construction Of a Bouncing Braneworldmentioning
confidence: 99%
“…Braneworlds [1,2,3] have generated enormous interest in higher-dimensional spacetimes amongst particle theorists. A key ingredient in these brane models is that the Standard Model particles remain confined to a (3+1)-dimensonal brane, while only the gravitational excitations propagate through the full spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…As solutions of gauged supergravity these are conjectured to be dual to the Renormalization Group (RG) flows of field theory couplings [7,8,9,10,11,12,13]. Domain Walls are also a key ingredient of Brane world construction [14,15,16,17,18,19]. More recently, in four dimensions, these solitons have been used as a laboratory for the comprehension of mirror symmetry in flux/generalized geometry compactifications [20,21,22] and to explore transitions between the different cosmological vacua of the Landscape [23].…”
Section: Introductionmentioning
confidence: 99%